Proceso de atención de enfermería en neonato de 60 horas de vida con hiperbilirrubinemia en el área de neonatología del Hospital General Martin Icaza. - Carrasco Vargas, Adrián Arturo (2020)
The purpose of this clinical case is to show the nursing care process in a neonate with hyperbilirubinaemia in the neonatology área of Martin Icaza General Hospital. Data collection was used in a suggestive way and through evaluation by physical examination which was of great importance for the diagnosis and the nursing process. The icterius is a common finding in newbors where yellow coloration in eyes, mucosus menbranes and skin additionally occurs frequently in a 60-70% of case of fullterm newborns and 80% of newborns bor prematurely. The icterius occurs when serum billirubin levels of >5mg/dl are elevated.